The tadpole of the Lake Oku clawed frog Xenopus longipes (Anura; Pipidae) - Tapley, Benjamin; Michaels, Christopher J; Doherty-Bone, Thomas M. (Zootaxa, 2015)
Xenopus longipes Loumont and Kobel, 1991 is an aquatic polyploid frog endemic to the high altitude crater lake, Lake Oku in North West region, Cameroon (Loumont & Kobel 1991). The tadpole of X. longipes is currently undescribed. So far, only dead tadpoles have been found at Lake Oku during regular monitoring since 2008 (Doherty-Bone et al. 2013), with specimens too decomposed to make adequate descriptions. Captive breeding provides one opportunity to obtain fresh specimens for description.